Особливості моделювання складових системи фінансово-економічного стимулювання впровадження передових технологій смарт-промислового розвитку - Turlakova, Svitlana S.; Shumilo, Yana M.; Logvinenko, Bohdan I. (Institute of Industrial Economics of NAS of Ukraine, 2023)
The introduction of advanced technologies by the Industry 4.0 phase at national enterprises is in the initial stages and requires economic support from the state. The system of financial and economic stimulation for the introduction of advanced technologies for smart-industrial development should combine monetary (monetary and credit) and fiscal (tax and budget) incentives. To ensure the validity and optimality of the choice of the list of such measures, it is relevant to build scenarios for the development of national industry using economic and mathematical modelling tools that allow assessing the impact of the identified incentives on the overall economic growth indicators.An analysis of the models by areas of incentives aimed at studying the impact of incentives on the economic performance of enterprises, industry or the overall economy of the States is carried out. The advantages and disadvantages of the DCF, VAR and GARCH models are outlined, which, along with the methods for assessing the effectiveness of individual incentives CBA, ROI, NPV, etc., may require modification to consider individual incentives, the introduction of additional factors and the accumulation of variables to assess the overall impact on the economy. Therefore, they are labour-intensive for solving the outlined problems, but can be used for intermediate calculations for certain incentive areas. For modelling the components of the financial and economic stimulation system at the national level, the most appropriate models are general economic models (Cobb-Douglas model, Solow model, AD-AS model, Samuelson-Hicks model, etc.). The modified Cobb-Douglas model, taking into account the digitalisation factor, reflects the dependence of production on the introduction of advanced smart technologies, has a number of advantages over other models and is technically convenient for long-term calculations, which is required for national industry development scenarios to assess the impact of the introduction of financial and economic stimulation for industrial development. Promising areas of research are outlined.